The Efficacy of the Comprehensive Use of Naphthalan and Non-Selective Chromotherapy in the Treatment of Patients with Gonarthrosis - Abramovich, Stanislav G.; Drobyshev, Victor A.; Koneva, Elizaveta S.; Makhova, Anna A. (Drug Research, 2020)
In the last decade, a new direction of phototherapy – the non-selective chromotherapy (NSC) with Bioptron – has become widespread in clinical physiotherapy. The aim of the study was the scientific justification of the comprehensive treatment of patients with osteoarthritis of knee joints, including the combined use of refined naphthalan applications and irradiation with incoherent polarized Bioptron light. The article presents the results of the study which investigated the efficacy of the comprehensive treatment of osteoarthritis of knee joints in patients using the combined exposure to naphthalan applications with irradiation using the non-selective Bioptron chromotherapy in the sanatorium. 64 patients aged 40–69 years with stage 1–3 knee osteoarthritis were examined and treated. It was shown that the combined use of naphthalan and non-selective chromotherapy in patients with gonarthrosis reduces pain, improves the functional state of the affected knee joints and improves the quality of life of patients in the absence of adverse effects. A comparative analysis of the study results showed that the efficacy of the combined use of naphthalan and non-selective chromotherapy is superior to the isolated effect of naphthalan.
Keywords: physiotherapy; bioptron; deforming osteoarthrosis; rehabilitation